Acquired aplastic anaemia after SARS-CoV-2 infection in China: a case report - Wu, Xiyan; Mo, Yi; Wen, Kailiang; Ming, Rui; Yin, Xinyu; Hu, Liang; Liu, Gang; Lin, Ge; Li, Weina (Frontiers in Pediatrics, 2023)
Since the coronavirus disease 2019 (COVID-19) pandemic began, several research groups in different countries have described cases of aplastic anaemia (AA) after COVID-19 or COVID-19 vaccination. Here, we present the case of a patient with new-onset AA in Changsha, China, that was presumably associated with preceding severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. We conducted an epidemiological assessment of the incidence rate of blood system diseases from July 1, 2022, to May 31, 2023, in the haematology department of the